Criminological Aspects Of The Crime Of Murder Committed By A Child Against Biological Parents : (Study of Decision Number 3/Pid.Sus-Anak/2022/PN Bnt) - Hutasoit, Ferry Fridolind; Sulistyawati, Sri; Pakpahan, Kartina (Fakultas Syariah INSURI Ponorogo, 2026)
This study examines the crime of murder committed by children against their biological parents (parricide) by focusing on the analysis of Decision Number 3/Pid.Sus-Anak/2022/PN Bnt from the perspective of criminology and Indonesian criminal law. The research method used is a normative juridical case study approach, based on the analysis of court decisions, laws and regulations, and criminological doctrines and theories. The results of the study showed that a combination of internal and external factors, such as prolonged family conflicts, domestic violence, psychological distress, emotional instability of children, and weak family supervision and parenting functions, influenced the occurrence of parricide. From a legal perspective, law enforcement against child offenders has referred to the provisions of the Criminal Code and Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, emphasizing the principles of child protection and rehabilitative punishment. From a criminological perspective, this case reflects the failure of the family as the main social environment. Therefore, comprehensive prevention efforts are needed to strengthen the role of the family, promote character education, and implement psychosocial interventions to prevent the recurrence of similar crimes.